Growth, chlorophyll and electric conductivity responses of rice cultivars to different levels of submergence and post- submergence stress - B.K. Dutta, R.K. Upadhyay, S.K. Panda (Journal of Phytology, 2009)
Submergence stress is one of the most adverse factors on plant growth and productivity. The present investigation evaluated submergence tolerance and susceptibility of rice (Oryza sativa L.) cultivars with root and shoot respond differently. The submergence tolerant and intolerant cultivars respond with better ability to synthesized reserve carbohydrates inducing the enzymes with hydrolyzing reserve polysaccharides. The increased percentage of electric conductivity indicated that the rice cultivars have better emergence ability on air adaptation. The MDA content was found to accumulate more after exposure to air than in submergence, which might be a sign of oxidative stress inducing free radicals. The present study revealed that submergence stress increased the membrane damage, as is evident from increased value of electrical conductivity and lipid peroxidation. The root and shoot physiology, as described above, presumably contributes to the ability of rice genotypes to grow in diverse environments that differ in submergence.